The Credit Investor's Handbook : Leveraged Loans, High Yield Bonds, and Distressed Debt - Gatto. Michael A. (Hoboken, New Jersey : John Wiley & Sons, 2024)
"The markets are vast and complex not only in the U.S. but globally. Everyone wants to make money. Yet, throughout the past years we have faced tremendous market swings rendering investors (and their money) in a sea of lost hopes, and few investors with a plethora of wealth. Many of these market anomalies and swings are dependent, and in a sense dictated, by the investor -- you. The investor sets the current stock price. The reaction of the investor determines the success of an IPO, an equity offering. Yes, the collective psychology of the market as a whole plays a major role, but if the everyday investor was better equipped with the proper tools to understand the underlying fundamentals of a rational investment, smarter investment decisions would be made, more rational investments will be made, and the markets would be a more efficient environment. This book sets to give any investor the fundamental tools to help determine if a stock investment is a rational one. The new edition of "Financial Modeling and Valuation" will be updated for 2020 and will be based on the new retail leader Amazon as opposed to Wal-Mart. A great introductory "thesis" to best transition from the old version to the new version will be based on the shift of the entire retail industry. There's a connection from old "mom and pop" produce companies of the early 1800s to the Great Atlantic and Pacific Company (A&P) to Wal-Mart, and now to Amazon in the progression of a "Retail Wheel". This is a great segway into the new book and can end with a though piece on where we will go next. Of course the focus of the book is technical but a couple of pages as an intro can give great context to the book. This book will give you the ability to build a financial model soup to nuts. You will not only build the core three statements - income statement, cash flow statement, balance sheet - but the three major supporting schedule necessary for full company valuation and analysis. A core explanation of each line item is included in addition to tips and techniques to use each line item as a tool to value and manage a business. Finally, applications are learned to fully understand a model's use including pricing a stock, raising debt, and raising equity"--
Includes index.
Keywords: Junk bonds; Debt